Internalization of Pesantren Values in Cultivating Students' Religiosity Subjects at SMA Darul Falah, West Bandung - Adi Suprihadi; Hasan Basri; Karman, Karman (al-Afkar, Journal For Islamic Studies, 2025)
This research is based on empirical phenomena observed by the researcher, where at SMA Darul Falah Bandung Barat, a school under the Yayasan Pondok Pesantren, there were still students who violated religious norms, such as not following school rules, skipping classes, and being late. The objectives of this research are to describe: 1) The programs for internalizing pesantren values in fostering the religiosity of students at SMA Darul Falah Bandung Barat; 2) The process of internalizing pesantren values in fostering the religiosity of students at SMA Darul Falah Bandung Barat. This research adopts a qualitative approach with a descriptive analysis method. Data were collected through interviews, observations, and documentation at the research location. The data analysis method used is the Miles and Huberman technique, a qualitative data analysis approach conducted interactively and continuously until data saturation is reached. The research findings are: 1) The internalization of pesantren values at SMA Darul Falah Bandung Barat is implemented through programs categorized by time, including spontaneous, daily, weekly, and annual/incidental programs. These programs are designed to build noble character, deepen religious understanding, and strengthen the spiritual bonds of the students; 2) The process of internalizing pesantren values occurs through three main stages: value transformation (changes in students' views and understanding), value transaction (active interaction between educators and students), and value transinternalization (integration of values into the students' selves). These three stages ensure that pesantren values are strongly embedded in the students' lives.